The potential of cellular homing behavior in tumor immunotherapy: from basic discoveries to clinical applications of immune, mesenchymal stem, and cancer cell homing - Li, Dongtao; Yang, Yixuan; Zheng, Guangda; Meng, Linghan; Shang, Lu; Ren, Juanxia; Wang, Lingyun; Bao, Yanju (Frontiers in Immunology, 2024)
The efficacy of immunotherapy, a pivotal approach in the arsenal of cancer treatment strategies, is contingent on the capacity of effector cells to localize at the tumor site. The navigational capacity of these cells is intricately linked to the homing behaviors of specific cell types. Recent studies have focused on leveraging immune cells and mesenchymal stem cells (MSCs) homing for targeted tumor therapy and incorporating cancer cell homing properties into anti-tumor strategies. However, research and development of immunotherapy based on cancer cell homing remain in their preliminary stages. Enhancing the homing efficiency of effector cells is essential; therefore, understanding the underlying mechanisms and addressing immune resistance within the tumor microenvironment and challenges associated with in vivo therapeutic agent delivery are essential. This review firstly delineates the discovery and clinical translation of the three principal cell-homing behaviors. Secondly, we endeavor to conduct an in-depth analysis of existing research on the homing of immune and stem cells in cancer therapy, with the aim of identifying and understanding of the common applications, potential benefits, barriers, and critical success factors of cellular homing therapies. Finally, based on the understanding of the key factors of cellular homing therapies, we provide an overview and outlook on the enormous potential of harnessing cancer cells’ self-homing to treat tumors. Although immunotherapy based on cell-homing behavior warrants further research, it remains a highly competitive treatment modality that can be combined with existing classic anti-cancer therapies. In general, combining the homing properties of cells to optimize their clinical effects is also one of the future research directions in the field of cell transplantation.